Optimized Extraction and Separation Conditions of Four Bioactive Compounds from Gelidium amansii - Tian, M.; Li, S.; Row, K.H. (Asian Journal of Chemistry, 2011)
The simultaneous extraction and separation of four bioactive compounds from Gelidium amansii were carried out through liquid-liquid extraction with a liquid chromatography separation. The optimum extraction conditions were established using different extraction solvents, procedures and times. The extracts were separated and determined using an analytical C18 column with a mobile phase consisting of acetonitrile-water (containing 1.0 % acetic acid) for a gradient elution of 0-30 min from 15:85-50:50 (v/v). Finally, total amount of 0.239 mg of four bioactive compounds was obtained from 1.0 g of Gelidium amansii.